Authenticity: Meanings, targets, audiences and third parties. (2021) - Carroll, Glenn R.; Kovács, Balázs
Abstract: Research shows that perceived authenticity conveys value in many disparate domains. The analytical attention of this research focuses on producers of products and services, identifying which actions and structures the typical individual associates with authenticity. Far less is known about how individuals and audiences differ in their interest, receptiveness and response to potentially authentic entities and services. Even less is known about how regulators, certifiers, critics and other third parties play a role in the social construction of authenticity. Yet the perception and valuation of a product or service as authentic rests largely with heterogeneous audiences and interpretive third parties. Accordingly, in this chapter, we review and develop theory and empirical research about how targeted entities (producers, persons, products, services), audiences and third parties combine to produce authenticity. For targets, we examine the range of actions and structures of various entities that have been empirically associated with authenticity. For audiences, we explore variations in interests in authenticity based on domain engagement, cosmopolitanism, and cross-cultural differences. For third parties, we consider the roles of other audience members, certifiers and regulators. Finally, we conceptualize a co-evolutionary process whereby targets, audiences and third parties combine to generate social pockets where authenticity is recognized and highly valued.